Generational Succession and Business Continuity in Micro and Small Family Businesses in the Textile Sector - Ticona - Apaza, Fiorela (2023)
Generational succession and its continuity is one of the biggest concerns of family businesses, constituting a problem that has generated the attention of many researchers and consultants. A large part of the founders and managers offamily businesses focus on the company’s operational process chain, including strategic plans, operational plans, control systems, etc.; and not worrying about succession plans that ensure the continuity of the company is undoubtedly a latent business risk factor. This work analyzes how the generational succession is related to the continuity of family businesses in the textile sector, being able to attribute that there are internal factors that affect continuity; however, it could also be verified if the company has elements or factors of competitiveness and attention to generational succession plans that generate interest in the family environment. After the application of the instrument, the results show us that, in effect, the generational succession influences the continuity of family businesses in the population studied and, therefore, the purpose set out in the study has been fulfilled.